The Ethnolinguistic Vitality of Konjo in Bulukumba Regency of South Sulawesi, Indonesia - Sri Ningsih; Hamzah Machmoed; Noer Jihad Saleh; Ria Jubhari (Hasanuddin University, 2021)
The maintenance of an ethnic language in a multilingual setting depends on many factors, and it is including language vitality. This study examines the vitality of the Konjo language in South Sulawesi. By demonstrating the ethnolinguistic vitality (EV) theory, this descriptive study examines Konjo language vitality in two contexts: ethnically homogeneous and ethnically heterogeneous areas in Bulukumba Regency. In the homogenous area, status, demographic, and institutional support are factors to contribute to the EV of Konjo. However, in the heterogeneous area, demographic factors contribute little while status and institutional support contribute to the maintenance of the language. The result of this study shows that the sheer number of Konjo community members distributed throughout the heterogeneous area is not sufficient for language maintenance. Nevertheless, Konjo EV remains high overall because of the community’s strong cultural and ethnic identification with their heritage language..